Impact of Canopy Suppression on the Eco-Taxonomic Structure of Weed Communities Associated with Gliricidia sepium in a University Campus in Benin City, Nigeria (Sahel Journal of Life Sciences FUDMA, 2026)
This study focuses on the use of Gliricidia sepium, where its canopy can suppress growth of weeds by preventing sun light. It seeks to understand how this affects weed diversity and composition for sustainability. The research aimed to investigate the impact of G. sepium on weed diversity in the built-up campus environment. Conservation sites and fields were surveyed, including the Department of Plant Biology and Biotechnology Botanical Garden, Bursary field, and Life Science Complex field. The study compared weed species in shaded (undisturbed) and unshaded (disturbed) environments under G. sepium canopy, and in open environments around the institution. Results showed that Gliricidia sepium morphometrics varied significantly by light environment. Trees in open areas achieved a higher average height of 8.5m compared to 7.62m for shaded trees. Conversely, shaded individuals demonstrated superior development in other metrics: a mean bole volume of 0.132m3 (versus 0.093m3) and a substantially larger canopy area of 50.72m2 (versus 36.83m2). This lateral expansion suggests adaptation for light capture. In distal zones 10m away, the ecosystem shifts toward sun-adapted species like Paspalum dilatatum (147 individuals) and Asystasia gangentica, confirming that the absence of canopy suppression allows light-demanding taxa to thrive. The results provide insights into the ecological dynamics of urban ecosystems and the role of introduced tree species in shaping plant community structure. The findings contribute to sustainable campus management practices, urban planning, and biodiversity conservation in tropical regions, offering valuable implications for ecologists, urban planners, and environmental managers seeking to optimize ecological benefits of urban green spaces.